HBV, HCV and HIV seroprevalence among blood donors in Istanbul, Turkey: how effective are the changes in the national blood transfusion policies? - Acar,Ali (2010)
The national blood transfusion policies have been changed significantly in recent years in Turkey. The purpose of this study was to determine the prevalence of HBV, HCV, and HIV in blood donors at the Red Crescent Center in Istanbul and to evaluate the effect of changes in the national blood transfusion policies on the prevalence of these infections. The screening results of 72695 blood donations at the Red Crescent Center in Istanbul between January and December 2007 were evaluated retrospectively. HBsAg, anti-HCV, and anti-HIV-1/2 were screened by microparticle enzyme immunoassay (MEIA) method. Samples found to be positive for anti-HIV 1/2 and anti-HCV were confirmed by Inno-Lia HCV Ab III and Inno-Lia HIV I/II Score, respectively. The seropositivity rates for HBsAg, anti-HCV, and anti-HIV-1/2 were determined as 1.76%, 0.07%, and 0.008%, respectively. Compared to the previously published data from Red Crescent Centers in Turkey, it was found that HBV and HCV seroprevalances decreased and HIV seroprevalance increased in recent years. In conclusion, we believe that the drop in HBV and HCV prevalence rates are likely multifactorial and may have resulted from more diligent donor questioning upon screening, a higher level of public awareness on viral hepatitis as well as the expansion of HBV vaccination coverage in Turkey. Another factor to contribute to the decreased prevalence of HCV stems from the use of more sensitive confirmation testing on all reactive results, thereby eliminating a fair amount of false positive cases. Despite similar transmission routes, the increase in HIV prevalence in contrast to HBV and HCV may be linked to the increase in AIDS cases in Turkey in recent years.